Measurement of the biomechanical function and structure of ex vivo drying skin using raman spectral analysis and its modulation with emollient mixtures. Issue 8 (28th August 2018) - Biniek, Krysta; Tfayli, Ali; Vyumvuhore, Raoul; Quatela, Alessia; Galliano, Marie‐Florence; Delalleau, Alexandre; Baillet‐Guffroy, Arlette; Dauskardt, Reinhold H.; Duplan, Helene
Abstract: An important aspect of the biomechanical behaviour of the stratum corneum (SC) is the drying stresses that develop with water loss. These stresses act as a driving force for damage in the form of chapping and cracking. Betasitosterol is a plant sterol with a structure similar to cholesterol, a key component in the intercellular lipids of the outermost layer of human skin, the SC. Cholesterol plays an important role in stabilizing the SC lipid structure, and altered levels of cholesterol have been linked with SC barrier abnormalities. Betasitosterol is currently applied topically to skin for treatment of wounds and burns. However, it is unknown what effect betasitosterol has on the biomechanical barrier function of skin. Here, by analysing the drying stress profile of SC generated during a kinetics of dehydration, we show that betasitosterol, in combination with two emollient molecules, isocetyl stearoyl stearate (ISS) and glyceryl tri‐2‐ethylhexanoate (GTEH), causes a significant modulation of the drying stress behaviour of the SC by reducing both the maximal peak stress height and average plateau of the drying stress profile. Raman spectra analyses demonstrate that the combination of betasitosterol with the two emollients, ISS and GTEH, allows a high water retention capacity within the SC, while the lipid conformational order by increasing the amount of trans conformers. Our study highlights the advantage of combining a biomechanical approach together with Raman spectroscopy in engineering a suitable combination of molecules for alleviating dryness and dry skin damage.